Ethnoecology of sotalia guianensis (gervais, 1853) in the Amazon estuar - Beltrán-Pedreros, Sandra; Petrere, Miguel [UNESP]; Filgueiras-Henriques, Ligia Amaral (My University, 2010)
This chapter describes a study conducted on the ecology of Sotalia guianensis in the Amazon estuary from 1999 to 2001, using participatory research with methodology. Interviews of 150 fishermen across 11 towns as well as surveys of the estuary by boat were completed to obtain information regarding S. guianensis in relation to their group size, habitat fidelity and calf-dynamics. Interactions between the ecological variables were tested using a log linear analysis of frequency tables for three factors. The results indicate that the S. guianensis is a gregarious species, forming groups of two or three individuals. However, groups with more than 10 individuals and herds of up to 150 were not rare. Group size was related to the behavior and kind of habitat used. In this study dolphins were commonly observed in large groups, feeding and swimming in open water habitats, however they were rarely observed in ports and near human communities. Habitats such as igarapés, lagoons and exposed coastal beaches were visited by the dolphins in the last hours of rising tide, high tide and the beginning of receding tide, when depth facilitated the exploration of the habitat. © 2010 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Amazon estuary.; Ethnoecology; Sotalia guianensis